PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt) PADA LAHAN GAMBUT YANG DIBERI ABU SEKAM PADI DAN TRICHOKOMPOS JERAMI PADI - Mohamad ' Seipin; Jurnawaty ' Sjofjan; Erlida ' Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The aim of this research was to determine the interaction of giving rice rush ash and straw trichocompost as well as the factors both on growth and production sweet corn plant on peatland and get the best dosage. This research was conducted at the experimental farm of the Agriculture Faculty, Rimbo Panjang, Kampar from February to May 2015. Thisresearch was carried experimentally using Randomized Block Design (RBD) factorial, the first factor is rice husk ash with 4 levels consisted of: 0 ton/ha, 3 ton/ha, 6 ton/ha and 9 ton/ha and second factor is straw trichocompost fertilizer with 4 levels consisted of: 0 ton/ha, 2,5 ton/ha, 5 ton/ha and 7,5 ton/ha. Each combination was repeated 3 times so there have 48 experimental units. Each experimental unit there have 24 plant and 5 plant as samples. The result of experiment that was obtained using analysis of variance were tested futher with Duncan’s New Multiple Range Test (DNMRT) at the 5% level. The result showed the aplication of rice husk ash 9 ton/ha and straw trichocompost 5 ton/ha are the best treatment for growth and production of sweet corn plant with production 7,21 kg/plot (equal with 16,02 ton/ha). Keywords:sweet corn, rice husk ash, straw trichocompost, peatland.